Do “fascismo de mercado” ao fascismo sem máscaras - Avelãs Nunes, António José (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2021)
In the 1970s, the so-called "thirty glorious years" vanished and the "miracle" of the Keynesian revolution was eclipsed. Taking advantage of the bewilderment of the 'enemy', the neo-liberals, led by Friedrich Hayek and Milton Friedman, went on the attack, putting the Keynesian state and Keynesian policies in the dock, blamed for all the ills of the world.Following an unparalleled ideological propaganda blitz ("a very corrupting experiment", Hayek confessed), ideological monetarism asserted itself as the ideology of empire and single-mindedness. Corrupting experiments like Hayek's have multiplied over the years, fuelled by the same actors, serving the same interests. And they continue to this day, with recourse to the most sophisticated techniques of ideological manipulation and intellectual corruption, which have transformed neoliberalism into a kind of 'religion', for whose "one true faith" it is said that there is no alternative (Mrs. Tatcher's famous TINA argument: There Is No Alternative).From this neutrality of economic policy we have moved, almost without a break in continuity, to the defence of the death of economic policy, because it would be unnecessary and harmful. It is the return to the old liberal myth of the separation state/economy and state/society: the economy would be the exclusive task of private individuals (civil society, economic society), with the state simply responsible for guaranteeing individual freedom, which would provide equal opportunities for all.
Keywords: fascism; world democracy; monetarianism; democratic policy